(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
This study aimed to evaluate fat content and fatty acid (FA) composition of desert sheep meat and adipose tissues at retail outlets in Khartoum State, Sudan. A total of 25 carcasses of desert sheep were used in this study. Samples from longissimus thoracic muscle (LT), kidney fat (KF), and subcutaneous fat (SF) were obtained from each carcass for fat extraction using chloroform-methanol method, and FA analysis using CG/ MS technique. The fat contents were 80.76, 75.57, and 4.02% for KF, SF, and LT, respectively. The most abundant FAs were oleic, palmitic, and stearic, which comprised about 81 to 87% of the total FAs. The highest portion of oleic acid was found in LT (29.2%) followed by SF (27.22%), and the lowest portion (22.12%) was found in KF. The portion of palmitic acid was significantly higher in KF (30.17%) compared to that in LT (27.03%) or in SF (26.73%). Stearic acid was significantly higher in SF (33.32%) compared to KF (29.2%) and LT (26.74%). The proportions of linoleic acid were 9.35, 4.2, and 1.6% for LT, SF and KF, respectively. The proportion of α-linolenic was significantly higher in LT (0.7%) than in SF (0.5%).The LT muscle had the highest level desirable FAs (67.36%), followed by SF (65.74%), whereas the KF had the lowest level (55.83%) of desirable FAs.